2009
DOI: 10.2298/sarh0912632r
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gluten-free diet on the growth and nutritional status of children with coeliac disease

Abstract: GFD applied for 1-3 years has a highly significant effect on the growth rate and nutritional status of children with the classical form of CD. Significant differences in these parameters of the disease were not detected between strictly compliant and non-compliant patients on GFD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 15 publications
1
24
0
4
Order By: Relevance
“…While catch-up growth with gluten elimination is observed in children, several studies reported that anthropometric measurements are not correlated with dietary compliance. 19 Radlovic et al, 20 compared patients who were fully compliant and noncompliant with GFD. They found that there was improvement in the weight, height, and hemoglobin levels, but a significant difference was not found between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…While catch-up growth with gluten elimination is observed in children, several studies reported that anthropometric measurements are not correlated with dietary compliance. 19 Radlovic et al, 20 compared patients who were fully compliant and noncompliant with GFD. They found that there was improvement in the weight, height, and hemoglobin levels, but a significant difference was not found between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, there is evidence that good compliance with GFD is associated with a positive effect on anthropometric parameters, including: the reduction of fat and the recovery of lean body mass [26], normalization of body mass index (BMI) in both previously underweight and overweight subjects [27] and acceleration of linear growth [28]. A study conducted in children with CD and obesity at diagnosis showed a significant reduction in BMI after 12 months of GFD [29].…”
Section: Effects Of Gluten-free Diet On Anthropometric Parametersmentioning
confidence: 99%
“…Some studies have recently evaluated anthropometric parameters in CD patients on GFD, with evidence, on the one hand, that good compliance with GFD is associated with recovery of fat and lean body mass (Barera et al ., ), body weight and acceleration of linear growth (Radlovic et al ., ) and also with normalisation of body mass index (BMI) in both previously underweight and overweight subjects (Cheng et al ., ), and on the other hand, that GFD may contribute to undesirabe weight gain and obesity (Mariani et al ., ; Dickey & Kearney, ; Valletta et al ., ). In obese children at diagnosis, a reduction in BMI has been observed after 12 months of GFD (Venkatasubramani et al ., ).…”
Section: Introductionmentioning
confidence: 99%